Current practice for social workers on planning contact for special guardianship children. Issue 4 (28th November 2019) - Thompson, Nicholas
Abstract : Purpose: An integral feature of Special Guardianship Orders (SGO) is that the children should have some contact with their parents after the order is granted. Local authority social workers have a duty to plan and recommend levels and types of contact. But there is no policy guidance provided on how to undertake these duties, and little is known about the process that practitioners undertake. The purpose of this paper is to investigate the recommending of contact in special guardianship cases, and to provide data on what contact social workers are recommending the factors they take into consideration and the reasons for their decisions. Design/methodology/approach: The research involved a mixed-methods approach comprising of a questionnaire and focus groups. This part of the study comprised of an online questionnaire that was completed by 102 local authority social workers. Responses were downloaded into SPSS Statistics v22 for data analysis and a content analysis was conducted. Findings: Quantitative results from the questionnaire are reported in this paper. Respondents provided comprehensive details on what they include in their recommendations, including levels of contact frequency and specific directions. Practitioners rated the factors they considered in reaching their decisions, and gave their general views on special guardianship contact. Results indicated that practitioners are recommending less contact for fathers than for mothers, and may feel less positively about paternal contact. Bivariate analysis suggests that some older and more experienced social workers are recommending lower levels of contact. Research limitations/implications: The statistical significance of the results was limited by the relatively small sample size. It was therefore decided to limit bivariate analyses to consideration of just three independent variables: the social worker's age and number of years in practice, and the age of the child at the time of their SGO, against dependent variables concerning the levels of contact that had been recommended for mothers and fathers and how positive these were considered to be. Because of the limited sample size, most of the results were above this level, and so were not statistically significant. Practical implications: Special guardianship has been in place for 12 years now, but apart from Jim Wade's 2014 study there has been no major research to guide and inform practice. Such major changes in child welfare require substantiating research, and this study is an attempt to begin filling that gap. The questionnaire part of this study has for the first time provided data on the views, motivations and practice of social workers across the country making recommendations on special guardianship contact. Social implications: The study provides a picture of the type of contact being recommended for birth parents. This information will be useful for practitioners, who might otherwise not know what their colleagues in other local authorities are recommending, and it is hoped that this will encourage further debate on the subject. Originality/value: Special guardianship has so far been poorly served by research. To the author's knowledge, apart from Wade's study there is very little research on the subject, and no significant research at all on special guardianship contact. This questionnaire, alongside the four focus groups that formed the second part of the study, provides the first picture of current practice across the country.